ChemInform Abstract: Perspectives on DNP‐Enhanced NMR Spectroscopy in Solutions. Issue 34 (4th August 2016) - van Bentum, Jan; van Meerten, Bas; Sharma, Manvendra; Kentgens, Arno
Abstract: Review: 81 refs.